Utilizing Chinese Videos as Promotion Strategy for Pancuran 7 Baturraden - Bagus Reza Hariyadi; Monika Herliana; Pradhika Ilham Parasdyatama Mardiyanto (Universitas Negeri Surabaya, 2024)
There are a lot of captivating natural tourism potentials in Banyumas Regency. One of them is Pancuran 7 (Pitu/Seven), which situated in the Banyumas Regency's Baturraden tourist region. Pancuran 7 is overseen by PT Palawi Risorsis, a company involved in several aspects of natural tourism, including trade, event organizing, agribusiness, agroindustry, outbound center, and tour travel. Pancuran 7 is renowned for its seven exquisite waterfalls that are found naturally. But there haven't been any international visitors, especially Chinese tourists, since the outbreak. To enhance the number of Chinese tourists visiting Pancuran 7 Baturraden, promotional videos in Mandarin must be produced. The following techniques are utilized to acquire data: internet browsing, literature study, documentation, interviews, and observation. The communicative method is employed by the author in translating. Subtitles and voiceovers were then employed by the author on the video. Producing a promotional film for Pancuran 7 Baturraden with Chinese voiceover and subtitles and posting it to modern social media platforms like Instagram and Tiktok is the end product of the work practice. The number of visitors from China is anticipated to rise as a result of these videos.